CERTAIN ISSUES OF RIGHTS CERTIFIED BY COMMON AND PREFERRED SHARES - Meliksetyan, Karen (State and Law, 2022)
This research is devoted to the analysis of the rights certified by ordinary and preferred shares issued by corporations (joint-stock companies), their content, domestic and foreign implementation mechanisms, the study of the implementation of different classes (types) of ordinary shares. The paper studies ordinary and preferred shares and their varieties in the context of changes and additions to the joint-stock legislation of the Republic of Armenia․ Also, emphasis is placed on new legislative regulations in connection with the provision of several types of ordinary shares and the features thereof․ In the light of the OECD standards and criteria, it is proposed to abandon the introduction of the mechanism of ordinary shares, which provide the owners of these shares with the right to more than one vote, since this jeopardizes the rights and legitimate interests of other owners of ordinary shares and violates the principle of justice. The legislative changes are based on the legislative regulations of foreign states on venture capital and angel investors, which, in fact, are not applicable to ordinary shares and the rights they certify․ At the same time, in the presence of the above regulations, some shareholders (owners of ordinary shares) get the opportunity to purchase ordinary shares with the right to more than one vote, including other privileges and additional benefits, at the same and/or low prices․ In this case, the balance of legitimate and fair interests of shareholders is violated․ As a result, it is proposed to refrain from the above institution and its mechanisms․